Hospitalized osteoporotic vertebral fracture increases the risk of stroke: A population‐based cohort study. (15th February 2013) - Chen, Yu‐Chun; Wu, Jau‐Ching; Liu, Laura; Huang, Wen‐Cheng; Cheng, Henrich; Chen, Tzeng‐Ji; Thien, Peck‐Foong; Lo, Su‐Shun
Abstract The association between osteoporosis and cardiovascular diseases has been demonstrated. Higher cardiovascular risk has also been correlated with vertebral fractures. However, the association between osteoporotic vertebral fracture and the possibly higher risk of stroke remains uncertain. This study aimed to evaluate the incidence, risk, and type of stroke in patients with osteoporotic vertebral fracture. Patients with osteoporotic vertebral fracture were identified (n = 380) and 10 age‐ and sex‐matched controls per case (comparison group, n = 3795) were chosen from a nationwide representative cohort of 999, 997 people from 1998 to 2005. Both groups were followed‐up for stroke events for 3 years, matched by propensity scores with adjustments for covariates such as comorbidities (ie, hypertension, diabetes, arrhythmia, or coronary heart diseases) and exposure to medications (ie, aspirin, lipid lowering drug, or nitrates), and assessed by Kaplan‐Meier and Cox regression analyses. The incidence rate of stroke in the osteoporotic vertebral fracture group (37.5 per 1000 person‐years; 95% confidence interval [CI], 27.5–51.2) was significantly higher than in the comparison group (14.0 per 1000 person‐years; 95% CI, 12.0–16.4, p < 0.001). Stroke was more likely to occur in the osteoporotic vertebral fracture patients than in the normal controls (crude hazard ratio [HR] 2.68, 95% CI 1.89–3.79, p < 0.001; adjusted HR 2.71, 95% CI 1.90–3.86, p < 0.001). In conclusion, patients with osteoporotic vertebral fracture have a higher risk of stroke (ie, both ischemic and hemorrhagic) and require stroke prevention strategies. © 2013 American Society for Bone and Mineral Research.